Enhanced performance of solid polymer electrolytes combining poly(vinylidene fluoride-co-hexafluoropropylene), metal-organic framework and ionic liquid for advanced solid state lithium-ion batteries - Macedo, V. M. (2024)
The search for sustainable and high-performance materials for lithium-ion batteries is leading to significant advances in solid polymer electrolyte (SPE) technology. However, the current drawbacks of this approach prove the need for further research and development in the field. Herein, novel ternary solid polymer electrolytes have been developed using varying loads of MOF-808 metal-organic framework and [BMIM][SCN] ionic liquid (IL) incorporated in a poly(vinylidene fluoride-co-hexafluoropropylene) matrix. The solid polymer electrolytes were evaluated at morphological, structural, thermal, mechanical and electrochemical levels, and their performance in cycling battery testing was assessed. The results showed a homogeneous structure throughout all the samples and a good dispersion of the distinct components. The polymer polar phase and degree of crystallinity of the samples are increased with increasing IL content, and the thermal and mechanical properties are appropriate for battery application. The ionic conductivity of the samples reaches maximum values of 4.68 × 10−5 S‧cm−1 at room temperature, lithium transference numbers up to 0.65, and high electrochemical stability, making them well-suited for battery applications. The assembled stability after 50 cycles at C/10 with a discharge capacity value of 150 mAh‧g−1 at room temperature was tested/derived. The obtained results show the potential of this system for high performance room temperature solid polymer electrolytes.